Investigação citogenética e molecular de casos de autismo atendidos em um ambulatório universitário no sul do Brasil - Jaime Lin; Fernanda Coan Antune; Lalucha Mazzucchett; Maiara de Aguiar da Cost; Cinara Ludvig Gonçalves (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: The term syndromic autism is used to refer to cases of autism spectrum disorder (ASD) that have a defined cause. A complementary investigation method for the etiological determination of ASD is neurogenetic investigation, and autism can have a hereditary behavior in up to 90% of cases. OBJECTIVE: The purpose of this article was to evaluate the occurrence of syndromic autism and the genetic characteristics involved in patients with ASD. METHODS: An observational, cross-sectional and retrospective study was carried out using data collected from the medical records of 135 children, aged between 2 and 15, who underwent genetic investigation and were diagnosed with ASD by the UNISUL Maternal and Child Ambulatory in Tubarão, Santa Catarina Brazil. RESULTS: According to the results of the genetic tests, 20% of the patients who underwent some type of genetic investigation changed and were included in the group of atypical autists. Among the patients who underwent the CGH Array exam 70.97% had some genetic alteration found, among those who underwent the karyotype 5.26% had changes, followed by 2.31% of the changes in the patients who underwent Fragile X DNA test. It was found that the presence of dysmorphism and microcephaly had statistical significance in the probability of alteration in the investigation. CONCLUSION: In the etiological assessment of autism spectrum disorder is important to carry out the genetic test. The karyotype, Fragile X DNA test and CGH Array detected the etiology in 20% of the children studied. In patients with some dysmorphism, the tests appear to be more sensitive.